ANALISIS JORAN BAMBU CENDANI TERHADAP LOYALITAS PEMANCING DI KOTA SUKABUMI: Manajemen Pemasaran - ENDANG NARYONO, SE., MM (P3M STIE PASIM Sukabumi, 2021)
Loyalty is the most important element in determining the progress of a product. To achieve the company's goals required a customer loyalty in accordance with the goals set. The purpose of this study was to analyze the effect of product, price, place, promotion, strength, flexibility, durability and artistic value of bamboo sandalwood rods in the city of Sukabumi. The population taken in this research is the anglers in the fishing pond in the city of Sukabumi, the sampling technique using purposive sampling is used as many as 100 respondents. This study uses primary data, namely data in the form of a questionnaire (a list of questions) which are distributed to respondents to be filled in and returned to the researcher. The data obtained were then analyzed using Multiple Linear Regression Analysis. The results of the regression analysis show that the magnitude of the significance of F = 0.000 < (0.05) means that together the variables are product (X1), price (X2), place (X3), promotion (X4), strength (X5), flexibility (X6 ), durability (X7) and artistic value (X8) have an influence on loyalty (Y). For the analysis of determination between independent variables consisting of product variables (X1), price (X2), place (X3), promotion (X4), strength (X5), flexibility (X6), endurance (X7) and artistic value (X8 ) has an influence on the dependent variable, namely the loyalty variable is known to be 58.0% while the remaining 42.0% is influenced by variables that are not examined.